The Effect of Sales Growth, Profitability, and Leverage on Earnings Management - Naue, Tresya Febrinasari; Anastasia, Yessi; Harjanto, Fariz Hutama Putra; Novyarni, Nelli (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2023)
The purpose of this study is to examine the effect of sales growth, profitability, and leverage on earnings management by using companies in coal mining sector registered on Indonesian Stock Exchange (IDX) for the period of 2017 to 2020. This research uses purposive sampling methods with predetermined criteria. The samples used in this study are 20 companies with a total sample of 80 data. This study is analysed using panel data regression in Eviews 10. The results demonstrate that sales growth and leverage partially have a significant effect on earnings management, while profitability has no significant effect on earnings management. Furthermore, sales growth, profitability and leverage simultaneously and significantly affect earnings management.